2012
DOI: 10.3354/meps09826
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the invasive grass Spartina anglica on benthic macrofaunal assemblages in a temperate Australian saltmarsh

Abstract: Reported impacts of the invasive saltmarsh grass Spartina anglica on benthic macrofaunal assemblages around the world vary considerably, and there is little understanding of the reasons for this variation. We compared macrofaunal assemblages and sediment characteristics among patches of S. anglica and adjacent uninvaded habitats (bare mudflat and native saltmarsh) in southeastern Australia. Invaded patches showed reduced species richness (by 50%) and diversity compared to both uninvaded habitats. Macrofaunal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 45 publications
4
8
0
Order By: Relevance
“…Even within such a short period, the impact of S. anglica on macrofaunal diversity and density was su ciently strong to produce signi cant effects. To some extent, these results are consistent with previous ndings obtained in a temperate Australian salt marsh (Cutajar et al 2012), and in Wenzhou Bay, China (Get et al 2012). Cutajar et al (2012) reported that invaded patches showed a 50% reduction in species richness, and reduced diversity, compared to two uninvaded habitats.…”
Section: Effect Of Spartina Invasion On Macrobenthic Communitiessupporting
confidence: 93%
“…Even within such a short period, the impact of S. anglica on macrofaunal diversity and density was su ciently strong to produce signi cant effects. To some extent, these results are consistent with previous ndings obtained in a temperate Australian salt marsh (Cutajar et al 2012), and in Wenzhou Bay, China (Get et al 2012). Cutajar et al (2012) reported that invaded patches showed a 50% reduction in species richness, and reduced diversity, compared to two uninvaded habitats.…”
Section: Effect Of Spartina Invasion On Macrobenthic Communitiessupporting
confidence: 93%
“…Spartina is a rhizomatous perennial grass that is highly invasive in German, Australian, Irish estuarine mudflats, sand flats and salt marshes 35 51 52 . The plant may reach a height of 50–100 cm, and its leaf blades are flat or in-rolled and 5–12 mm wide.…”
Section: Methodsmentioning
confidence: 99%
“…With vague rationalizations of possible value, S. anglica was introduced to Australia during the first half of the twentieth century. Introductions ceased by 1962, and concerted control with herbicides has been practiced in recent decades (Cutajar et al 2012). The most recent large invasion stems from the purposeful introduction of S. alterniflora in China, where the consequences are beginning to be assessed (Strong and Ayres 2013).…”
Section: Herbicidesmentioning
confidence: 99%